1995
DOI: 10.1111/j.1460-9568.1995.tb01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Populations of Identified Glial Cells in the Developing Rat Spinal Cord Slice: Ion Channel Properties and Cell Morphology

Abstract: Four types of glial cells could be distinguished in the grey matter of rat spinal cord slices at postnatal days 1-19 (P1-P19), based on their pattern of membrane currents as revealed by the whole cell patch clamp technique, and by their morphological and immunocytochemical features. The recorded cells were labelled with Lucifer Yellow, which allowed the subsequent identification of cells using cell-type-specific markers. Astrocytes were identified by positive staining for glial fibrillary acidic protein (GFAP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 53 publications
11
110
2
Order By: Relevance
“…This identification was confirmed by the lack of action potential in response to depolarizing current injections, the absence of spontaneous electrical activity, and the negative resting potential (ϽϪ70 mV). Furthermore, in voltage-clamp mode, the absence of typical off-set currents indicated that these cells were not oligodendrocytes (Chvatal et al, 1995). When whole-cell recording of a glial cell was performed with a biocytin-filled pipette, this intercellular tracer was detected in surrounding cells after fixation and biocytin revelation (Fig.…”
Section: Characterization Of Astrocytic Network In the Barrel Cortexmentioning
confidence: 99%
“…This identification was confirmed by the lack of action potential in response to depolarizing current injections, the absence of spontaneous electrical activity, and the negative resting potential (ϽϪ70 mV). Furthermore, in voltage-clamp mode, the absence of typical off-set currents indicated that these cells were not oligodendrocytes (Chvatal et al, 1995). When whole-cell recording of a glial cell was performed with a biocytin-filled pipette, this intercellular tracer was detected in surrounding cells after fixation and biocytin revelation (Fig.…”
Section: Characterization Of Astrocytic Network In the Barrel Cortexmentioning
confidence: 99%
“…1A), electrophysiological characterization of membrane properties, and labeling with Lucifer yellow or Alexa 594 in a number of cells and confirming ultrastructure post hoc. Neocortical astrocytes are known to be relatively small cells, with cell bodies in the range of 6 -15 m. This size criterion was the basis for the initial selection of an experimental cell; identity was also established electrophysiologically: astrocytes are characterized by their high negative resting membrane potentials (RMPs), low input resistances, and passive, linear currentvoltage relationships (e.g., Chvatal et al 1995;D'Ambrosio et al 1998;Schwartzkroin and Prince 1979;but see Bordey and Sontheimer 1998). Based on these electrophysiological criteria, we characterize the cells in this study as neocortical astrocytes.…”
Section: Identification/characterization Of Cellsmentioning
confidence: 99%
“…On the other hand, glial cells could be recognized because they had hyperpolarized resting potentials (Ϫ87.8 Ϯ 2.9 mV), lower resistance (33 Ϯ 16 m⍀; n ϭ 5; see refs. 19 and 20), and were unable to elicit full action potentials in current-clamp mode (21). The current run-down protocol adopted was the following: after current amplitude stabilization with repetitive applications every 120 s, a sequence of 10 GABA applications every 15 s was delivered.…”
Section: Membrane Preparation and Injection Proceduresmentioning
confidence: 99%